The Effect of Work-Life Balance, Work Discipline, and Work Environment on Job Satisfaction with Teacher Performance as an Intervening Variable - Heri Prabowo; Dimas Juli Pratomo; Ika Indriasari (Universitas Mercu Buana, 2023)
Objectives: Based on the previous statement, this study aims to examine and analyze the effect of work-life balance, work discipline, and work environment on teacher job satisfaction and teacher performance. The population of this study were elementary school teachers in Tegowanu District. The number of samples in total is 69 respondents. Methodology: The sampling technique used is simple random sampling. The data analysis technique used is PLS-SEM (Partial Least Square-Structural Equation Model) analysis. Research data processing using Smartpls 3.0 tools was conducted. Findings: In accordance with the results above, it shows the results of the direct influence test where the majority have a P-Values value of less than (0.05) meaning that it has the influence of endogenous variables on exogenous variables. However, some are not affected because they have a P-Values value greater than (0.05).Conclusion: Based on the results of the study, it was found that work-life balance had an effect on teacher performance with a P-Value of (0.03). Work discipline has no effect on teacher performance with a P-Value of (0.090). The work environment has an effect on teacher performance with a P-Values of (0.41). Teacher performance has an effect on job satisfaction with P-Values (0.000). Work-life balance has an effect on job satisfaction which is mediated by teacher performance with a P-Value of (0.014). Work discipline has no effect on job satisfaction which is mediated by teacher performance with a P-Value of (0.098)